Imposition Of Criminal Sanctions In The Case Of The Crime Of Child Abuse By A Mother Suffering From Baby Blues Syndrome: Study Decision Number 296/Pid.B/2018/Pn.Kwg - Amalia Kemala Dewi; Subekti Subekti; Riska Andi Fitriono (International Journal of Law and Society, 2024)
The writing of this article aims to analyze postpartum mental health disorders can be categorized as psychiatric disorders for reasons of criminal expungement and analyze the imposition of criminal sanctions in the criminal act of child abuse by mothers who suffer from baby blues syndrome in the Karawang District Court Decision Number 296/Pid.B/2018/PN.Kwg. The type of research used is normative with a statutory approach and a case approach. Based on the results of research conducted by the author, it is obtained that postpartum mental health disorders can basically be used as an excuse for criminal erasure in accordance with the severity experienced. The imposition of imprisonment by the judge in the case of child abuse by a mother with mental health disorder in the verdict was not appropriate because the judge did not pay attention and consider the condition of the perpetrator of the crime who suffered from mental health disorders of a fairly severe type and level.